La transparencia de información del buen gobierno corporativo y el cumplimiento de objetivos comerciales de los bancos inscritos en la Bolsa de Valores de Lima - Gadea Avila, Jazmín Anais Zuleica (2018)
The present research arose in order to determine the relationship between the compliance with the Principles of Good Corporate Governance of Pillar V "Transparency of Information" of the "Report on compliance with Good Corporate Governance" and the commercial objectives’ achievement from the Banks that are listed on the Lima Stock Exchange between 2014, 2015 and 2016; In this sense, the research was carried out a descriptive scope, fourteen Banks listed on the Lima Stock Exchange were sampled, this sample was calculated using the multistage probabilistic method. The analysis consisted of measuring the degree of compliance with Good Corporate Practices regarding Pillar V in relation to Bank customers and comparing it with the number of claims for asymmetry of information and compliance with business objectives by analyzing the variation of operating income and net income of these entities. The result obtained was that there is not enough evidence to show a relationship between the variables, since it was found that the Banks that increased their compliance with the Principles of Good Corporate Governance of Pillar V did not necessarily show an increase in the achievement of their commercial objectives. However, if a couple of customer-oriented principles were specifically implemented in said Pillar, the results obtained would reveal that If less information is provided to the client, then these entities generate higher revenues.